Strålende afhandling om sort racial isolation - Lene Myong (Kvinder, Køn & Forskning)
Review of Elizabeth Löwe Hunter Black Racial Isolation: Understanding African Diaspora Subjectivity in Post-Racial Denmark, University of California, Berkeley, 2023, PhD Dissertation